Penggunaan Media Video Animasi Permainan Tradisional Bakiak Untuk Peningkatan Keterampilan Motorik - Dinar Ayu Mirunggan Sari; Murtono Murtono; Irfai Fathurohman (STKIP Andi Matappa Pangkep, 2021)
Games are something that can not be removed from the world of children. Traditional games are generally played in the field, yard, plataran, and othe places. At this time the traditional game began to be defeated with games that use technology (today’s games). Today’s games tend to keep children quiet and not move from place to place. This causes students motor skills to be poorly felt and less likely to stay in place. Motor skills are related to the development and process of controlling gestures (large musle work) in composed activities including nerves, brain, muscles, and spinal cord. The purpose of this study was to describe the use of traditional video game animation media for motor skills improvement. Researchers use qualitative. Data collection techniques in this study are observation, interview, questionnaire, and documentation. The result of this reseacrh is the utilization of traditional game animation video media for motor skills improvement.